Application of software and hardware components of CAN-technology for accelerator control - Chepurnov, A.; Nedeoglo, F.; Etenko, A.; Sabelnikov, A. (Вопросы атомной науки и техники, 2004)
CAN-technology was developed for embedded hard real time automotive applications. CAN-bus together with
high-level application protocols is used now to control large experimental installations and particle accelerators.
CAN-technology includes fieldbus, universal and specialized controllers, sensors and actuators. Software
components of CAN-technology consist of high level application protocols, programs for testing, monitoring and
configuring of CAN-nodes as well as the components which bind CAN-components with SCADA systems and
ensure control through the WEB-browsers. CAN-technology is used in INP to control accelerators, for beam
diagnostic and, in cooperation with the RRC Kurchatov Institute, in automation of the large neutrino detector
Borexino. CAN-bus adapters for PC have been constructed. Such software components as drivers for PC adapters,
the bus emulator and protocol analyzers have been developed under Linux. Original specialized high level protocols
have been developed for closed specialized systems. Source codes have been developed and verified for
compatibility with international standards such as DeviceNet and CANopen for use in the systems that are supposed
to be extended with commercially available software and hardware components. Long-term positive experience of
CAN-technology usage allows us to recommend this technology for accelerator control especially if industrial style
and compatibility is desired. CAN технологія була розроблена для застосування як убудовану мережу жорсткого реального часу для
автоелектроніки. У НІДЯФ МГУ технологія CAN застосовується для контролю і керування
прискорювачами, діагностики пучка і, разом із РНЦ Курчатовський Інститут, для автоматизації великого
нейтринного детектора Borexino. Багаторічний позитивний досвід роботи з CAN і експлуатація систем
керування з CAN дозволяє рекомендувати цю технологію для побудови систем керування прискорювачами. CAN технология была разработана для применения в качестве встроенной сети жесткого реального
времени для автоэлектроники. В НИИЯФ МГУ технология CAN применяется для контроля и управления
ускорителями, диагностики пучка и, совместно с РНЦ Курчатовский Институт, для автоматизации большого
нейтринного детектора Borexino. Многолетний позитивный опыт работы с CAN и эксплуатация систем
управления с CAN позволяют рекомендовать эту технологию для построения систем управления
ускорителями.